Analysis of Economic Structure and Leading Sectors in Rejang Lebong District - Anadiya Pingki; Bambang Sumantri; Ketut Sukiyono (AGRITROPICA : Journal of Agricultural Sciences, 2021)
This study aims to determine and analyze the economic structure and leading sectors in Rejang Lebong Regency. The data used is secondary data on Gross Regional Domestic Product from 2015 to 2019 obtained from the Central Statistics Agency. The analysis used is economy structure, Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift-share, and Overlay. The results show that the highest GRDP contributor is the Agriculture, Fisheries, and Forestry sectors while the lowest is the Electricity and Gas Procurement sector  with contribution of 32% and 0.15% respectively. The results of the leading economic sectors in the Rejang Lebong Regency are the sectors of Agriculture, Forestry and Fisheries, Providing Accommodation and Food and Drink; Defense and Compulsory Social Security; Education Services; Health Services and Other Services.